The COVID-19 Pandemic: Invoking the Famine and Pestilence Clause to be Paired with the Medicine Chest Clause from the Numbered Treaties - Bourassa, Carrie; Starblanket, Danette; Langan, Jennifer; Hagel, Mikayla; Anderson, Sadie; Legare, Marlin; Chapados, Meghan (The International Indigenous Policy Journal, 2021)
Treaty-based strategies are required to address the unique needs of Indigenous communities in Canada during the COVID-19 pandemic. A treaty-based approach should recognize provisions within the Numbered Treaties, including the Famine and Pestilence Clause and Medicine Chest Clause, agreed to during the signing of Treaty 6 in 1876. The Famine and Pestilence Clause established the Crown’s obligation to aid Indigenous Peoples within Treaty 6 Territory in the event of calamities such as locust raids, storms, starvation, and disease. The Medicine Chest Clause instituted the means through which the Crown would provide medical care for Indigenous Peoples within the jurisdiction. The Government of Canada has a legal obligation to invoke the Famine and Pestilence Clause and Medicine Chest Clause in a strategy to address the spread of COVID-19 in Indigenous communities.